Pengaruh Pendidikan Kewirausahaan, Kompetensi Guru dan Motivasi Berwirausaha Terhadap Minat Siswa dalam Berwirausaha - Dani Herdiyana; Vip Paramarta; Theresia Widyanti (Departement of Mathematics Education, 2024)
Students' interest in entrepreneurship reflects more than just a desire to earn a living. The aim of this study is to comprehensively analyze the impact of entrepreneurship education and teacher competence on students' entrepreneurial interest through entrepreneurial motivation at SMKN 1 Gunungguruh, Sukabumi Regency. The evaluation was conducted using descriptive and inferential methods, involving 83 students as the research sample. Data processing was performed using Smart PLS 4 software. The study's results showed that entrepreneurship education and teacher competence did not affect students' entrepreneurial interest, while entrepreneurial motivation had a significant impact on students' entrepreneurial interest. Furthermore, entrepreneurship education, teacher competence, and entrepreneurial motivation collectively influenced entrepreneurial interest. This research provides important insights into the factors that influence the formation of entrepreneurial interest among students at the vocational high school level. The findings' implications can be used as guidelines for developing more effective strategies and policies in education management and student empowerment within the educational environment.